Personal growth through English proficiency: a case study in Sarawak - Chan, Siaw Leng; Kapong, Joyce Morris (Akhmet Yassawi University, 2021)
Globally, English is known as the most spoken language. In Malaysia, learners may face challenges in learning English as a second language; however, the capability to master the language is believed to be able to develop one's personal growth. Essentially, personal growth in learning involves a continuous change in behaviour, attitudes, and values. Therefore, this case study aimed to understand the learners' personal growth through English proficiency development. A qualitative case study design using a semi-structured interview was utilised to investigate personal growth experiences in English proficiency development. Interviews were conducted as the most compelling way to understand the participants' narrative descriptions and subsequently uncover the meaning of their values, beliefs, and experiences. Data collected was analysed using Morse's four stages of analysis to extract the essence of the participants' lived experiences. Five themes emerged as personal growth experienced by the learners, namely, the courage to take risks, individual values in diversity, enriched interpersonal relationships, cognitive adjustment, and positive attitudes. The findings provided educators with some indications and a holistic view of the learners' lived experiences of personal growth through English proficiency development which is often an overlooked issue during the teaching and learning process.